Deep Soil Mixing Column Supported At-Grade Track Slab and Single-Span Bridge Transit Structures. Issue 1 (1st February 2017) - Brignall, Kelly; Ding, Yuming
Abstract: The Evergreen Line rapid transit project (ELRTP) is located in the lower mainland of British Columbia, a region that is prone to earthquakes. The transit line travels along a dedicated right-of-way through three municipalities and has varying site conditions. A 1.8 km long segment of the line travels at-grade and is founded on liquefiable soils that are likely to experience lateral spreading displacements during the design seismic event. To mitigate the risk of large lateral spread, ground improvements were done by constructing deep soil mixing (SMX) columns to support the at-grade guideway. During the design development, steel pipe piles were also considered for support of the track slab. SMX columns were chosen due to construction efficiencies and their ability to meet the repairable damage performance requirement. SMX columns are constructed by auguring cement slurry into the soil. The guideway structure is composed of a continuously reinforced concrete track slab, and includes twin, single-span precast box-girder bridges, which span over a creek. During a seismic event, there is potential for loss of soil support below the track slab between the multi-column SMX panels. The slab is designed to span consecutive SMX panels and will remain elastic under lateral seismic loading.